Relação entre os investimentos em TIC e a evolução patrimonial das cooperativas agropecuárias do oeste do Paraná - Bortoluzzi, Franciane (2016)
Agricultural cooperatives are challenged to position and to remain competitive in a globalized economy scenario. In this sense, this thesis objective was to analyze the relationship between investments in information and communication technology and the asset developments of the agricultural cooperatives from the west of Paraná. This study is justified by the importance that information represents in the decision-making process of agribusiness managers. Moreover, drastic reductions in the cost of obtaining, processing and transmitting information are changing the way of doing business. In highly competitive times, increasing efficiency in the use of information and communication technology is essential to business sustainability. The methodology of the study is qualitative, because it analyzed the management reports from the last 20 years of the cooperatives operation (secondary data), which were crossed with the information obtained in the interviews (primary data) with the ICT managers of these organizations, and quantitative, because statistical analyzes and correlation tests were applied in the data. The results showed that the efficiency used in the entire production chain can yield better profitability and that the cooperatives with the highest percentage of ICT investments also have higher results in net assets. The tests show a correlation between ICT investments and the evolution of the results of most cooperatives studied